Assessment in the Workplace Environment by Working Student in a Selected Fastfood Chain in Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Nowadays, the fast food chain is the most popular restaurant today, and that’s why manypeople eat here because of the affordable price and high service quality to provide thecustomer needs. There are various types of fast food restaurants, and each of them has aunique specialization to satisfy their customers. In this generation, many students haveworked in fast-food chains to earn money and support their studies. Working in fast food is agood way to gain experience and meet different types of people. Being a working student is aresponsibility because they have to divide their time between study and work. Living as aworking student is stressful, most likely balancing their social life, time for family and friends,and also things that they want to do in their lives.Based on the results of the study, most working students struggle to balance their work andstudy, which leads to stress and poor performance.Working with students is really a hassle. There's so much struggle, especially how to managetheir time. They should have set priorities and have proper schedules to fulfill all theresponsibilities between school and work, and they also need to have self-discipline when itcomes to managing the time they have to balance their stress.
Keywords: Hospitality Management